The Influence of Competence, Work Motivation and the Working Envi-ronment on Employee Performance at the Oku Regency Youth and Sports Agency - Rudi Gunawan; Yunita Sari; Mardiah Kenamon (Institute for Law and Economics Studies, 2026)
This study aims to analyze the influence of competence, work motivation, and work environment on employee performance at the Ogan Komering Ulu Regency Youth and Sports Office. The research method used is a quantitative descriptive approach with a causal design. The population in this study consists of all 47 employees, who were selected as the sample using a census technique. Data collection was conducted through questionnaires and documentation, while data analysis utilized multiple linear regression with the aid of statistical software. The results indicate that, individually, competence, work motivation, and work environment each have a positive and significant effect on employee performance with a significance level of < 0.05. Collectively, these three variables also have a significant effect on employee performance. The coefficient of determination (R²) value of 0.413 indicates that 41.3% of the variation in employee performance can be explained by competence, work motivation, and the work environment, while the remainder is influenced by other variables outside the research model. These findings indicate that enhancing competencies through training, strengthening work motivation, and creating a conducive work environment are critical factors in improving employee performance, particularly in supporting the effectiveness of public services within government agencies